On the Effects of Developers' Intuition on Measuring Similarity Between UML Models - Gonçales, Lucian José; Farias, Kleinner; Bischoff, Vinicius (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Software design models play a key role in many activities of information systems engineering, such as documenting software artefacts, communicating project decisions, and code generation. In this scenario, the techniques for comparison of software design models are used for several purposes, such as, for detecting clones, and model evolution. In the last decades, academia proposed different techniques for comparing software models. Even using these different techniques for model comparison, this process is still an activity of a subjective nature, because during this process, different developers can interpret the similarity differently. Thus, the problem is that it is still unknown if developers has the same intuition in order to resolve comparison of software design models. For this, the main objective of this work is to explore the effects of their experience level, i.e., experienced and inexperienced developers, relative to their effort and correctness for resolving activities of comparing software design models. Therefore, a controlled experiment was conducted to evaluate the developer's experience level regarding on similarities of UML Models. The results show that the developer's experience does not affect the understanding of similarities activities.